Cosmopolitanism and Irish foreign policy : a case study analysis - Ward, Eilís (Trinity College (Dublin, Ireland). Department of Political Science, 2000)
This thesis sets out to explore cosmopolitanism as a position within International Relations theory in the context of the activism of Irish Non-governmental Organisations (NGO) in Irish foreign policy. NGOs are posited as espousing a cosmopolitan activism in their attempts to influence Irish foreign policy makers. The methodology adopted was primarily a case study approach allowing an intensive analysis of three foreign policy issues: East Timor, the Enhanced Structural Adjustment policy of the International Monetary Fund and the Beijing Fourth World Conference on Women, 1995. In addition, the thesis also features the results of a survey of the NGO landscape in Ireland. In all, a total of 61 NGOs were surveyed on organisational, strategic and normative dimensions to their work.
Keywords: Politics, Ph.D.; Ph.D. Trinity College Dublin